Assessment of the medical radiation and non-radiation risks for the patients undergoing the surgical gender reassignment from female to male - V. V. Safronov; A. A. Davydov; A. V. Vodovatov; O. I. Startseva; A. M. Biblin; L. V. Repin (Радиационная гигиена)
The aim of the current study was to perform a comparative assessment of the radiation and non-radiation health risks for the sample of transgenders as well as the assessment of their perception of these risks. The study was performed on the sample of patients, undergoing the gender reassignment surgery from female to male. The structure of surgical procedures and the corresponding X-ray examinations was analyzed with the subsequent assessment of the radiation and non-radiation health risks. The level of patient knowledge on the risks and benefits of the medical procedures and perception of the ratio of radiation and non-radiation risks were evaluated based on the results of the sociological study. The study included the patients that underwent gender reassignment surgery in August 2012 – February 2018 on the base of I.M. Sechenov First Moscow State Medical University. Data collection and questioning were performed in August 2019 – March 2020. Data on the structure of the surgical procedures and X-ray examinations was collected for 99 patients; 86 patients agreed to participate in the questioning. The results indicate that the selected sample of patients, undergoing the gender reassignment surgery from female to male, is a high risk group both for radiation and non-radiation factors. For the whole multi-stage gender reassignment surgery, a patient could receive a total effective dose up to 250 mSv due to repeated computed tomography scans of chest, abdomen and head with contrast, corresponding to the lifetime attributive radiation risk of up to 1×10-2. Comparison of radiation and non-radiation risks for that patient sample indicates the dominance of the risk of successful suicide attempts (5×10-2). Radiation risks are equal to or even exceed (for the final stages of the gender reassignment surgery) the other risks of mortality from the non-radiation factors (anesthesia – 5,4×10-5, thrombosis – 2×10-5, post-surgical complications – 6×10-2). The reduction of suicide risks, as a result of the treatment, outweighs all other risk factors and justifies the gender reassignment surgery. The results of a sociological study show a decrease from 77% to 23% of suicidal thoughts among the patients. The study indicates that risk-communication was performed on the unsatisfactory level: less than 40% of the patients were informed about the possible health risks during the treatment; less than 50% of respondents knew about the benefits of X-ray examinations. About 70% of the patients rate their current problems with health higher compared to the risks from diagnostics and surgery. It explains the lack of interest to the radiation risk.